How does the experience and destination authenticity influence “affect”? - Loureiro, S. M. C. (Anatolia, 2020)
The current study aims to explore how tourist experience and destination authenticity influence intentions to revisit and to recommend through positive and negative affect. The proposed model is tested in the city destination context. The questionnaire was handed to tourists who had stayed in Lisbon for vacations. A sample of 210 questionnaires is employed to analyse the model. Findings mainly reveal that (i) tourist experience has a stronger affect on negative affect than on positive affect, (ii) positive affect has a mediator and significant role between destination authenticity and revisit intentions, (iii) learning is the most relevant in shaping the overall tourist experience and (iv) existential authenticity is the most effective in creating the overall destination authenticity.